Predicting which people with psychosocial distress are at risk of becoming dependent on state benefits: analysis of routinely available data - Whittaker, Will (BMJ Publishing Group Ltd., 2010)
Objectives To examine whether there was significant variation in levels of claiming incapacity benefit across general practices. To establish whether it is possible to identify people with mental health problems who are more at risk of becoming dependent on state benefits for long term health problems based on their general practice consulting behaviour. Design Interrogation of routinely available data in the Scottish Health Surveys and the British Household Panel Survey. Setting Scotland and the United Kingdom. Participants Respondents to the Scottish Health Surveys in 1995, 1998, and 2003 (7932, 12 939 and 11 472 respondents, respectively). Respondents to the British Household Panel Survey, 1991-2007 (more than 5000 households). Main outcome measures Intracluster correlation coefficient for probability of work incapacity by general practice. Caseness according to the general health questionnaire (GHQ-12) and frequency of consultation with general practitioner in years before and after starting to claim incapacity benefit. Results There was a small and non-significant amount of variation across general practices in Scotland in rate of claims for incapacity benefit after adjustment for other explanatory variables (intracluster correlation coefficient 0.01, P=0.135). There was a significant increase in rates of GHQ-12 caseness from two years before the start of claiming incapacity benefit (odds ratio 1.6, 95% confidence interval 1.3 to 1.9) and an increase in frequent consultation with a general practitioner from three years before the start of claiming incapacity benefit (1.8, 1.3 to 2.4). People with GHQ-12 caseness showed a significant increase in frequent consultations with a general practitioner from two years before the start of claiming incapacity benefit (2.1, 1.4 to 3.2). Conclusions There was no variation in levels of claiming incapacity benefit across general practices in Scotland after adjustment for differences in population characteristics and so initiatives targeted at practices with high levels are unlikely to be effective. People with mental health problems who are likely to have problems remaining in work can be identified up to three years before they transit on to long term benefits related to ill health.